Trade on the North Eastern Bank of the Lagos Lagoon: A Focus on Ejinrin Lagoon Market, 1851–1939 - Oladipo O. Olubomehin (Yoruba Studies Review, 2021)
This article discusses trade and market activities on the north eastern bank of the Lagos Lagoon. Our particular focus is on the Ijebu lagoon market of Ejinrin. During the period covered by this study, Ejinrin was a meeting point for traders from Lagos and those from southeastern Yoruba hinterland. Traders reportedly attended the market not only from Ijebuland but also from places such as Gbongan, Ile-Ife, Ilesha, Oyo, Ilorin, Okitipupa, Owo, Epe, Orimedu, Atijere and other towns in Yorubaland. Colonial records show that attendance at Ejinrin reached between 20,000 and 26,000 on a market day by the end of the nineteenth century and by 1908, the market was rated as the largest market in the whole of the western provinces of Nigeria. Such was the strategic importance of this market that it supplied Lagos with the bulk of the palm oil shipped overseas during the pre-colonial and colonial periods. Thus, the lagoon market occupied a very important place in the local economy of the Ijebu and that of Lagos. This article is an attempt to understand this aspect of the indigenous economy of Nigeria. It is an attempt to analyze and document the history of commercial activities in this geographical zone of the Lagos (Ijebu) Lagoon. The study relied largely on documentary evidence got from the National Archives, Ibadan and extensive oral evidence collected from those who, at one time or the other, had attended the market.